FACTORS AFFECTING THE CHOICE OF TANGIBLE FIXED ASSET ACCOUNTING METHODS: THEORETICAL APPROACH - Zinkeviciene, Danute; Vaisnoraite, Giedre (European Scientific Journal, ESJ, 2014)
The research is designed to identify factors that determine the management decisions to choose one or the other tangible fixed asset accounting method. The article offers a systematic analysis of factors determining the choice of tangible fixed asset accounting methods that is based on research by Lithuanian and foreign scientists and hypotheses of the positive accounting theory. The research produced a theoretical result: it identified groups of factors that determine the choice of tangible fixed asset accounting methods including a flow chart of the factor and accounting method interaction, which can be used to develop a profit increasing or profit decreasing accounting policy. The factors are broken down into factors of the internal and external environment. Financial and human factors are attributable to the internal environment factors, while economic and technological factors are regarded as factors of the external environment. It was found that the financial leverage and the firm value maximization are the key factors in the financial factor group as they affect the management determination to opt for profit increasing tangible fixed asset accounting methods, while technological factors have an effect on profit decreasing tangible fixed asset accounting policy choice. Economic (the national economic situation and factors of the political process, such as the size of the company, its profitability, and the industry branch it belongs to) and human factors provide an opportunity to use both: profit increasing or profit decreasing tangible fixed asset accounting methods. The research results will contribute to a most correct choice of the tangible fixed asset accounting methods by the company management, appropriate management decisions, and achievement of the objectives.